2005
DOI: 10.1017/s0260210505006479
|View full text |Cite
|
Sign up to set email alerts
|

Between power and hegemony; business communities in peace processes

Abstract: The support that businessmen and business organisations displayed for the peace processes in Israel and Northern Ireland was open and vocal, underscoring the supposed linkage between globalisation, peace and economic growth, and the supposed leadership role of business. The purpose of this study is to examine the motivations of the business communities in Israel and Northern Ireland in becoming involved in the peace processes, their organisation to promote peace, decision-making processes at critical junctures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The study also found that after an initial phase of political involvement, the business community seemed to withdraw from politics and refrain from organized intervention. 10 Conversely, in Russia during its transition period from communism, liberal elites with an interest in peace and a smooth transition to a globalized market economy prevailed over other elites more prone to conflict. Specifically, political and economic winners in Russia's transition pursued foreign policies that avoided international conflicts because they stood to gain the most from peaceful foreign relations.…”
Section: Business Business Power and Peacementioning
confidence: 99%
See 2 more Smart Citations
“…The study also found that after an initial phase of political involvement, the business community seemed to withdraw from politics and refrain from organized intervention. 10 Conversely, in Russia during its transition period from communism, liberal elites with an interest in peace and a smooth transition to a globalized market economy prevailed over other elites more prone to conflict. Specifically, political and economic winners in Russia's transition pursued foreign policies that avoided international conflicts because they stood to gain the most from peaceful foreign relations.…”
Section: Business Business Power and Peacementioning
confidence: 99%
“…Within Israel, this concept indicated a paradigmatic shift among policy makers and bureaucrats away from the conceptualization of the conflict as inevitable, permanent, or intractable. 17 Accordingly, the NME provided a blueprint for the future of the region based on economic rationality, peace, democracy, cooperation, mutual gain, and general prosperity.…”
Section: Business and Peace-jordan And Palestinementioning
confidence: 99%
See 1 more Smart Citation
“…the Single European Market) pre-date or are quite independent of the GFA (see Anderson 1994). Economic interests are particularly important, though as Guy Ben-Porat (2005) found in the different contexts of Northern Ireland and Israel, business lobbyists may have only limited influence on peace processes partly because of being politically divided or elitist. However, the key thing which the institutions can facilitate is not so much lobbying for peace (which simply adds yet more actors focusing on the ethno-national conflict), but rather the development of actual political communities which themselves cross the ethnic and territorial divides and thereby (perhaps inadvertently) undermine or displace the very basis of the conflict.…”
Section: An Over-polarised Debate and The Good Friday Agreementmentioning
confidence: 99%
“…Like in the European Union, it was argued, the economic transformation would introduce new interests, a new rationality and a "zeitgeist" that at once was both inevitable and desirable for the Middle East to follow (Ben-Porat, 2005a). These ideas were well received by Israel's liberal elites, whose desire to "normalize" Israel was translated into a three-part agenda that included economic and political liberalization, termination of the conflict, and global integration (Ben-Porat, 2005c). While the Israeli economy had been on a rapid path of liberalization since the mid-1980s, the continuation of the conflict was perceived as impeding economic progress and holding back Israel from the path of globalization.…”
Section: Oslo and The New Middle East -Top-down Orientationmentioning
confidence: 99%